Positive leadership and adding value – a lifelong journey. Issue 2 (8th May 2017) - Cameron, Kim; Quinn, Robert E.; Caldwell, Cam
Abstract : Purpose: Kim Cameron and Robert Quinn are two widely admired world class scholars at the University of Michigan's Ross School of Business. The purpose of this paper is to explore their personal views about positive leadership and added values over the traditional approach to organizations and leadership. Design/methodology/approach: This interview was designed to obtain personal insights to positive leadership from world renowned leadership scholars. Findings: Most people do have something to give that is worthwhile, when they address the question of positive leadership over traditional leadership. The moment we orient people to their highest purpose, there is an incentive for them to close their integrity gap. Originality/value: Obtaining personal insights from lifelong scholars of leadership by means of personal interviews is paramount in the professional field of leadership.